Adsorption of pH-sensitive peptides on self-assembled lipid membranes - Chiarpotti, María V. (2022)
Experiments have shown that the pH is low in the vicinity of tumor cells. The acidity contrast between diseased and healthy tissues offers the possibility of developing pH-sensitive chemical markers that allow the identification and treatment of tumors. In particular, peptides possessing pH-Sensitive amino acids can be used as vehicles to introduce therapeutic and contrast agents into cancer cells. In this work, we present a model based on Molecular Theory [1] that allows us to study the adsorption and insertion of pH-sensitive peptides in lipid membranes. In particular, we focus on a set of cyclic peptides developed by Weerakkody et al. that is effective in the identification and treatment of tumors [2]. Peptides and lipids are described by a coarse-grained model based on the MARTINI force field. A free energy functional is proposed whose minimization leads to the self-aggregation of lipid molecules to form a membrane, and to the spatial distribution of peptides and ions through the lipid/solution interface. Our methodology considers electrostatic and steric interactions, entropic effects, and the acid-base equilibrium of all titratable molecules. In addition, the theory considers the shape, charge distribution, and conformations of lipids and peptides. First, we characterize the membrane self-assembly. Second, we characterize the adsorption and insertion of two cyclic peptides, c[E4W5C] and c[R4W5C], and a linear peptide, l[CW(EW)4], as a function of the pH of the solution. Two lipid membranes are considered, a neutral and a titratable one. The results are presented at pH 3 and 8 ensuring the complete charge transition of glutamate residues. Our results allow us to test the adsorption mechanism of the peptides, which are compared with experimental data [2].